Constructions Collocations Patterns - Herbst, Thomas; Schmid, Hans-Jörg; Faulhaber, Susen (Trends in Linguistics. Studies and Monographs TiLSM., 2014)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> This volume, which has textbook character, is intended to provide an in-depth introduction to different theoretical and methodological research frameworks concerned with the role of item-specific grammatical and lexical behaviour.